Milling Machine Stand Table Design Using DFMA Method : (Design For Manufacture And Assembly) - Dimas Irfan Putra Firman Pamungkas; Ardana Putri Farahdiansari; Faisal Ashari (Journal of Social Science and Economics, 2022)
Milling machine is a machine tool that produces a plane where a blade rotates and a moving object does feeding step. While milling is a machining process which generally produces a flat shape due to the movement of from the machine table, where the workpiece material reduction process occurs due to the contact between the cutting tool (cutter) which rotates on the shaft with the workpiece gripped on the machine table. table design This machine aims to facilitate a job and process production. This design uses the Design For Manufacture method and Assembly (DFMA). (DFMA) is a method in the manufacture of products that aim to facilitate the manufacturing process of assembly where existing designs may be simplified and adapted to the capabilities of the manufacturing facility with considering technical aspects. That way there will be some changes in terms of design, addition of components, and convenience to the when used. So that there will be new breakthroughs that are more effective and efficient. Getting the ergonomics of the milling machine table to be very good comfortable to use